Common mental health outcomes and access to support services among adolescents living with HIV in sub-Saharan Africa: a protocol for a systematic review - Kwaku Oppong Asante; Emmanuel Nii-Boye Quarshie; Delight Abla Klutsey; Margaret Amankwah-Poku (BMJ Open)
Introduction The prevalence of HIV in adolescents is a major global health concern, and research into the influence of HIV on mental health outcomes in this demographic is ongoing. We will conduct a comprehensive systematic review of common mental health outcomes in adolescents with HIV infection (aged 10–24 years). Recognising the specific psychosocial issues that adolescents living with HIV infection are confronted with, this review aims to integrate existing research on the prevalence, risk factors and protective factors related to both positive and negative mental health outcomes in this population.Methods and analysis The following electronic databases will be searched for publications from 1959 up to December 2025: PubMed, PsycINFO, Global Health, Embase, African Journals OnLine and African Index Medicus. The review will focus on both positive and negative mental health outcomes: positive outcomes include resilience, subjective happiness and post-traumatic growth, whereas the negative outcomes include depression, anxiety, post-traumatic stress disorder, substance use disorder and suicidality. Peer-reviewed primary observational studies that report prevalence rates for common mental health outcomes outlined in the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition, and the International Classification of Diseases, 11th Edition, their associated factors, as well as barriers to and facilitators of use of mental health support services among this population, will be included in the review. Google Scholar and ProQuest Dissertations & Theses Global as well as Electronic Theses and Dissertations from Ghana, South Africa, Uganda and Kenya, will also be searched for grey literature. The review will be limited to publications in English or French. To assess the methodological rigour of the selected studies, the Joanna Briggs Critical Appraisal Tools will be used. The synthesis will include a narrative summary and, if applicable, a meta-analysis of quantitative data depending on the extent of heterogeneity observed in the included studies. Subgroup analyses will be conducted to investigate differences in mental health outcomes by age, sex and socioeconomic position, where applicable. This systematic review will be reported in accordance with the PRISMA statement.Ethics and dissemination This review will use secondary data and does not require ethical approval. The findings will be shared through peer-reviewed publications and conference presentations. The emphasis will be on translating research findings into practical mental health interventions and HIV-specific support services for adolescents.PROSPERO registration number CRD42024568512.